A new species of Curtara DeLong & Freytag (Insecta: Hemiptera: Cicadellidae) from Middle Western Brazil - Coelho, Luci Boa Nova; Da-Silva, Elidiomar Ribeiro (Zootaxa, 2012)
The Neotropical genus Curtara DeLong & Freytag (Cicadellidae: Iassinae: Scarinae) includes more than 160 described species, with 40 of them recorded from Brazil (Coelho & Da-Silva 1996; 2002). DeLong & Triplehorn (1978) erected the subgenus Curtara (Labata) for C. basala DeLong & Triplehorn from Paraguay. Later, DeLong (1980) included in this subgenus C. xingua DeLong from Xingu, Mato Grosso State, Brazil.